Пошаговое объяснение:
1)
-1,22÷х=6,1
х=-1,22÷6,1
х=-0,2
2)
-8,9÷(-х)=11,57
-х=-8,9÷11,57
-х=-8целых 9/10 ÷ 11целых 57/100
-х=-89/10 ÷ 1157/100
-х=-89/10×100/1157
-х=-1/1×10/13
-х=-10/13
х=10/13
3)
9,6÷(-у)=-43,2
-у=9,6÷(-43,2)
-у=9целых 3/5 ÷ (-43целых 1/5)
-у=48/5 ÷ (-216/5)
-у=48/5×(-5/216)
-у=2/1 × (-1/9)
-у=(-2/9)
у=2/9
Пошаговое объяснение:
1)
-1,22÷х=6,1
х=-1,22÷6,1
х=-0,2
2)
-8,9÷(-х)=11,57
-х=-8,9÷11,57
-х=-8целых 9/10 ÷ 11целых 57/100
-х=-89/10 ÷ 1157/100
-х=-89/10×100/1157
-х=-1/1×10/13
-х=-10/13
х=10/13
3)
9,6÷(-у)=-43,2
-у=9,6÷(-43,2)
-у=9целых 3/5 ÷ (-43целых 1/5)
-у=48/5 ÷ (-216/5)
-у=48/5×(-5/216)
-у=2/1 × (-1/9)
-у=(-2/9)
у=2/9